L’inexistence de Dieu dans la phénoménologie de la donation de Jean-Luc Marion - Vinolo, Stéphane (Teología y vida, 2024)
Jean-Luc Marion’s phenomenology of givenness has become well-established within philosophy and theology since the demise of metaphysics reopened the possibility of analyzing the existence of God from a phenomenological perspective. However, his phenomenological approach poses a serious challenge. Since God is no longer the God of metaphysics, the phenomenon of God can no longer be based on a modality of presence but rather on one of absence or retreat. By analyzing the three different kinds of invisibility in the phenomenology of givenness, the author shows, that far from the invisible and the unseen, the phenomenality of God must be conceived as the manifestation of an absence. This conception is, therefore, not the negativity of nonexistence nor the negativity of nonbeing but rather the positive paradox of nonexistence.